2020
DOI: 10.1016/j.mehy.2020.110051
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing adenosine A2A receptors as a strategy for suppressing the lung inflammation and thrombotic complications of COVID-19: Potential of pentoxifylline and dipyridamole

Abstract: Counterproductive lung inflammation and dysregulated thrombosis contribute importantly to the lethality of advanced COVID-19. Adenosine A2A receptors (A2AR), expressed by a wide range of immune cells, as well as endothelial cells and platelets, exert cAMP-mediated anti-inflammatory and anti-thrombotic effects that potentially could be highly protective in this regard. The venerable drug pentoxifylline (PTX) exerts both anti-inflammatory and antithrombotic effects that reflect its ability to boost the responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 100 publications
(103 reference statements)
0
22
0
4
Order By: Relevance
“…NAC is approved by FDA under various formulations and is popular as a health supplement, this molecule having been proposed as a nutraceutical that might aid the control of RNA viruses including influenza and coronavirus. [64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Discussionmentioning
confidence: 99%
“…NAC is approved by FDA under various formulations and is popular as a health supplement, this molecule having been proposed as a nutraceutical that might aid the control of RNA viruses including influenza and coronavirus. [64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Discussionmentioning
confidence: 99%
“…Given that prostacyclin has beneficial effects in platelets and the endothelium by increasing cAMP levels, other oral agents that raise cAMP levels in these cell types might also be potential therapeutic strategies for COVID-19. These include the phosphodiesterase 3 inhibitors, such as dipyridamole and cilostazil, which are currently used for stroke prevention and peripheral vascular disease [251][252][253] . A small study has suggested a benefit of dipyridamole in patients with COVID-19, showing a reduction in biomarkers of disease severity (such as d-dimer levels) and improved clinical outcomes 252 .…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…Modulation of TNFα , IL1, IL6, ICAM1, VCAM1 and TNF, as well as inactivation of PDE and prevention of platelet aggregation are among the proposed mechanisms that could aid as treatment options for moderate to severe COVID-19 patients. (5,6,8,13,25,26) PTX has proven to be useful in patients with ARDS, from different etiologies and to improve pulmonary function and control pulmonary fibrosis. (27)(28)(29), Furthermore, the potential of pentoxifylline as a therapeutic agent is warranted as there is little to no downside in using this drug because of a safe adverse effect profile and a low cost.…”
Section: Discussionmentioning
confidence: 99%
“…(4) As a result, investigators have proposed alternative drugs with multiple mechanisms of action in light of finding a lower rate of complications from this disease, and potentially lower the mortality. Pentoxifylline (PTX) is a methylxanthine derivative, currently used for peripheral vascular disease, with anti-inflammatory and immunomodulatory properties (5)(6)(7). Moreover, the main pharmacodynamic properties of this drug are aimed at improving circulation by increasing erythrocyte deformability.…”
Section: Introductionmentioning
confidence: 99%